3. Iannis Xenakis in Berlin - Marko Slavíček (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
The Greek-French avant-garde composer and architect Iannis Xenakis was mostly active in Paris throughout his creative life. However, as a young artist, he took part in a year-long residency in Berlin, where he engaged deeply in artistic and theoretical work. This period proved fruitful, as he formulated certain aspects of his aesthetics in the domains of both music and architecture. After the residency, the composer continued to return to the city following various engagements for more than three decades. This chapter presents an overview of Xenakis’s activities in Berlin throughout his career, as well as the role the city played in his professional life. These activities include architectural competitions, lectures, workshops, musical compositions, and theoretical writings. I also examine the role Berlin-born conductor Hermann Scherchen had in the composer’s breakthrough, the works created during the Berlin residency, Xenakis’s connections to the Technical University of Berlin, and his membership of the Berlin Academy of Arts. To reconstruct the chronology of events, I rely on archival materials such as personal letters, newspaper reviews, flyers, videos, and sound recordings. In the end, we do not only see how Berlin became a pivotal element in Xenakis’s biography but also how the city has kept the composer’s legacy alive through numerous cultural events.